2006
DOI: 10.1063/1.2207718
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of local Seebeck coefficient in M∕T∕M and M∕T∕M∕T∕M (M=Cu or Ni and T=Bi or Bi0.88Sb0.12) composite materials

Abstract: &petaanee of the-uinfoitunate victims of vitilikoiis striking, nd scid"y failsto evoke a etelig bf hrr aid pitY-At th6 afflikttd, W 9e; condit"on, isdeemed incurable. The pict1uie of af ot1i1s4 a!e, reoved frj9r typical sooty negro's skin, marked with spots perfectly. white, and, from the CQ^1, trast, appearin!1'fireri-than the skiii of the fairest European, must, to evineyn fi rhiarisd'to the siht, appeart iepugnant. These spots vasw9'from a i;Sre (spe:k'to several inches in size, ahd, in advanted ca.ses, tl;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(122 citation statements)
references
References 15 publications
6
97
1
4
Order By: Relevance
“…The cells were cultured for another 3 days in the presence of only the cytokines present in the initial culture. The numbers of Th1/Th2 cells were determined by using intracellular staining with anti-IL-4 and anti-IFN␥ as described (10).…”
Section: Methodsmentioning
confidence: 99%
“…The cells were cultured for another 3 days in the presence of only the cytokines present in the initial culture. The numbers of Th1/Th2 cells were determined by using intracellular staining with anti-IL-4 and anti-IFN␥ as described (10).…”
Section: Methodsmentioning
confidence: 99%
“…Although (Fe,Cr) 3 O 4 forms as the inner scale or in the internal oxidation zone, it cannot be seen by XRD. In our previous studies, 4) metallic Ni particles were observed at the interface of the duplex scale. As we will show later, Ni diffraction spectra come from metallic Ni particles which are located beneath the observed at the Cr 2 O 3 /steel interface.…”
Section: Methodsmentioning
confidence: 99%
“…Yamashita et al 4) examined oxidation tests of the solution treated Fe20Cr30Ni2Nb (at%) austenitic steel at 973 K in both air and steam atmospheres. The same oxidation tests were also carried out by using pre-aged sample in which intermetallic compounds precipitated.…”
Section: Introductionmentioning
confidence: 99%
“…115) And then they obtained the shape after buckling by the large deformation analysis using the FEM. Ishikawa & others 116) and Yamashita & others 117) examined the occurrence of cross buckling by using the FEM under the assumption that it was caused by the shear stress. Komori and others analyzed too the occurrence of cross buckling by the energy method under the assumption that the elastic buckling occurred continuously at the micro domain by the residual stress.…”
Section: Expansion Of Application Of the Finite Elementmentioning
confidence: 99%
“…The analysis for the slight reduction rolling appeared here and there in the past. The analysis in which the material was assumed to be elasticplastic and the roll flattening deformation was taken into account by modification of Orowan's and Karman's researches, 120,121) and the analysis to use the dislocation theory of the continuation distribution 122) were announced. These researches for the slight reduction rolling were performed as the 2-dimensional problem, but it may be still said that there was considerable progress in handling the materials as elastic-plasticity from rigid-plasticity.…”
Section: Expansion Of Application Of the Finite Elementmentioning
confidence: 99%